(untitled) (Dhaka Shishu (Children) Hospital Journal, 2021)
Background: Guillain-Barré Syndrome (GBS) deserves a serious attention in children. The treatment of GBS consists of supportive and immune-modulator treatments, among which intravenous immunoglobulin (IVIG) is considered as most effective. But IVIG is costly and many patients cannot afford. Objective: To document the outcome of treatment of GBS patients by IVIG and Methylprednisolone. Methods: This is a retrospective study conducted in the Pediatric intensive care unit of Dhaka Shishu Hospital from January 2013 to December 2016. Data was collected from the admission record file in pediatric intensive care unit of Dhaka Shishu Hospital. A total of 36 patients up to the age of 15 years presenting with Guillain-Barré Syndrome were included in the study. Treatment modalities including supportive, Intravenous Immunoglobulins (IVIG) and steroids were selected in patients with GBS depending upon indication and facilities available. Those who were unable to provide IVIG due to financial constrain were treated with Methylprednisolone. Results were analyzed using SPSS (version 16) for Windows. Results: During the study period, a total of 36 patients were diagnosed and treated as GBS in pediatric intensive care unit. Among those, 34 (94.4%) patient were classical GBS. Most patients were in the age range of 3-5 years (21, 58.3%). Total 19 (52.8%) patients were treated with IVIG and rest was treated with steroid (17, 47.2%). 16 (44.4%) patient needed mechanical ventilation and among the patient needed mechanical ventilation 9 (56.3%) got treatment with IVIG and 7 (43.7%) got treatment with Methylprednisolone. After treatment 31 (86.2%) patients were improved and 5 (13.8%) were expired. Among the improved patient 16 (84.2%) were treated with IVIG and 15 (88.2%) were treated with Methylprednisolone. Conclusion: Treatment outcome of GBS patient with Methylprednisolone is comparable with IVIG and can be considered in case of financial constrain. DS (Child) H J 2018; 34(1) : 30-35